Customer Perceived Value in Ethnic Japanese Restaurants: Which Factors are Considered? - Desi Urdianti; Ika Nurul Qamari; Wan Hasmat Wan Hasan (ETIKONOMI, 2023)
Ethnic restaurants are currently a fascinating topic, as they promote specific ethnic cultures and provide customers with a chance to try something new and different. Ethnic restaurants often offer flavours that are truly representative of a certain culture. This research investigates the factors that influence customer perceived value in Japanese ethnic restaurants. Data were collected through an online survey completed by customers who had visited a Japanese ethnic restaurant, Marugame Udon, in Indonesia. The Structural Equation Model (SEM) was applied to test the hypotheses. The findings of this study demonstrate that food quality, employee service quality, and price fairness positively affect customers’ perceived value. In contrast, the dining atmospheric quality and restaurant authenticity do not affect customers' perceived value. Studies on customer perceived value in ethnic Japanese restaurants are still incredibly rare in the literature., especially in Indonesia and Malaysia. Thus, this study aims to fill that gap, providing valuable insights for future research and restaurant management.JEL Classification: M10, M11, M21How to Cite:Urdianti, D., Qamari, I.N., & Hasan, W. H. W. (2023). Customer Perceived Value in Ethnic Japanese Restaurant: Which Factors are Considered? Etikonomi, 22(2), 457 – 472. https://doi.org/10.15408/etk.v22i1.30641.